2011
DOI: 10.1002/marc.201190045
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Rapid Commun. 17/2011

Abstract: Back Cover: Polyalkylenehydroxybenzoates (PAHBs) represent a new class of biorenewable aromatic/aliphatic polyester. These thermoplastics derive from lignin‐based aromatic feedstocks and their thermal properties can be tuned to closely match those of petroleum‐based polyethylene terephthalate. Further details can be found in the communication by L. Mialon, R. Vanderhenst, A. G. Pemba, and S. A. Miller* .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Unlike the homopolycondensation of AB-type phydroxycinnamic acids derivatives (22)(23)(24)(25)(26)(27), the copolycondensation of bisphenols and diacyl chlorides allows to expand the range of T g values thanks to a greater structural flexibility. In fact, by playing with both the chain length of the diacyl chloride and the structure of the internal diol of the bisphenols, one can tailor the T g of these bio-based polymers from 0 to 76°C.…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the homopolycondensation of AB-type phydroxycinnamic acids derivatives (22)(23)(24)(25)(26)(27), the copolycondensation of bisphenols and diacyl chlorides allows to expand the range of T g values thanks to a greater structural flexibility. In fact, by playing with both the chain length of the diacyl chloride and the structure of the internal diol of the bisphenols, one can tailor the T g of these bio-based polymers from 0 to 76°C.…”
Section: Thermal Analysismentioning
confidence: 99%
“…Many research groups have recently demonstrated the great potential of ferulic acid-derived AB-type monomers through the development of new homopolyesters exhibiting appealing thermal properties through either metal-catalyzed polycondensation (22)(23)(24)(25), oxalyl- (26) or thionyl-chloride-(27) activated polycondensations. Other homo-and copolyesters of natural p-hydroxycinnamic acids showing remarkable liquid-crystal (28)(29)(30)(31)(32)(33)(34)(35), biodegradability (36,37) or biocompatibility (30) properties were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…13 Perhaps the most successful, fully biorenewable polyester is polylactic acid (PLA), made from corn starch or other carbohydrates. Recreating this hard/soft motif with bioaromatics from lignin (vanillin) or lignocellulose (ferulic acid, coumaric acid), our research group [19][20][21][22] has reported several new biogenic polyesters and copolyesters with T g values ranging from 78°C to 153°C, 22 surpassing the important benchmark of 100°C for polystyrene (PS). 17 PET exhibits a notably higher T g of 67°C, 18 making it suitable for a wider range of applications.…”
mentioning
confidence: 99%
“…16 Additional saturation and flexibility were introduced by subsequent hydrogenation of hydroxyethylferulic acid (n = 2) and hydroxyethylcoumaric acid (n = 2), affording hydroxyethyldihydroferulic acid and hydroxyethyldihydrocoumaric acid monomers, respectively. The hydrogenation of the double bond in ferulic acid or p-coumaric acid is one approach for incorporating the necessary conformational flexibility into the polymer main chain.…”
mentioning
confidence: 99%